Effect of fabrication parameters on the pore concentration of the aluminum metal foam, manufactured by powder metallurgy process - Ozan, Sermin; Bilhan, Seda (Springer London Ltd, 2008)
In this paper, the effect of fabrication parameters on the pore concentration of aluminum metal foam manufactured by powder metallurgy process is studied. Aluminum metal foam specimens were fabricated from the mixture of aluminum powders (mean particle size 60 mu m) and NaCl at 10,20,30,40(wt) % content under 200, 250, 300, MPa Pressures. All specimens were then sintered at 630 degrees C for 2.5 hours in an argon atmosphere. For pore formation (foaming), sintered specimens were immersed into 70 degrees C hot running water. Finally the pore concentration of specimens was recorded to analyze the effect of fabrication parameters (namely NaCl ratio, NaCl particle size and compacting pressure) on the foaming behavior of compacted specimens. As a result of the study, it has been recorded that the above mentioned fabrication parameters are effective on pore concentration profile while pore diameters remained unchanged.
Keywords: aluminum metal foam; fabrication parameters; pore concentration